Fracture Modeling of Deep Tight Sandstone Fault-Fracture Reservoir Based on Geological Model and Seismic Attributes: A Case Study on Xu 2 Member in Western Sichuan Depression, Sichuan Basin - Li, Jitong; Liu, Junlong; Chen, Hongde; He, Jianhua; Wang, Ruyue; Shao, Xupeng; Fang, Xin (Geofluids, 2023)
With significant geological reserves and high resource abundance, the Xujiahe Formation in the Western Sichuan Depression is considered a key target for natural gas exploration and development in continental clastic rocks within the Sichuan Basin. However, this formation remains underdeveloped. Critical to forming “sweet spots” of tight reservoir is the presence of fractures. Based on available data sources, including core samples, well logs, and outcrop data, we utilized a combination of geophysical and geological modeling techniques to clarify the characteristics of effective fractures in tight gas reservoirs. This allowed us to construct a geological model of a tight sandstone fault-fracture gas reservoir in the Xu 2 Member of the Xujiahe Formation located in the Xinchang area, which represents a fault-fracture reservoir formed by high-angle faulting-derived fractures and controlled by the S-N trending fault. With this model, a variety of seismic attributes, including likelihood and entropy, was used to predict the fault-fracture reservoir. Furthermore, geological information, well logs, and seismic attributes were integrated for characterizing the fractures of different scales. The cutoff on various attributes for characterizing the fault-fracture reservoir was defined, and the distribution of the fault-fracture reservoir was delineated. By using the geological modeling technique, the fracture model of the fault-fracture reservoir comprising natural fractures at different scales was built. This model provides further guidance for the exploration and development of the Xu 2 Member tight gas reservoirs in the Xinchang area and, as demonstrated by drilling results, has achieved remarkable effects in practice. This approach has shown good performance in characterizing fracture models. However, due to the complexity of fractures and the discrepancy between the scale of fractures and the scale that can be predicted by geophysical methods, there may still be some uncertainties associated with this method.